Implementation of Fair Trade in Rice Trading Through the Circular Economy Concept to Realize Environmental Welfare and Sustainability - Moratama, Ferdinan (LITIGASI, 2025)
The World Bank pays attention to the high price of rice in Indonesia, because the increase in rice prices is not balanced by the improvement of the welfare of rice farmers. To reduce rice production costs, the use of chemical pesticides is an option because of its more affordable price and quick results. Farmers in general have a weak position in obtaining production facilities, financing farming businesses, and getting fair prices. Looking at these conditions and situations, a concept emerged known as fair trade or commonly known as the concept of fair trade. However, the concept of fair trade has not been explicitly regulated in Indonesian trade law. This legal research was carried out using a qualitative analysis method with a conceptual approach. The results of the study show that, with the implementation of fair prices and fair business practices, it can support the implementation of circular economies that have an impact on the welfare of rice farmers and increase the awareness of rice farmers to protect the environment. In addition, the existence of fair trade can shift the rice production chain which currently weakens the position of rice farmers and burdens high purchase prices on consumers. The implementation of fair trade can also maintain national food security. Therefore, arrangements are needed regarding the implementation of fair trade in rice trade in Indonesia and the commitment of government apparatus to socialize, implement, supervise, and certify fair trade in Indonesia.